Na+/K+-ATPase interaction with methylglyoxal as reactive metabolic side product - Svrckova, Marika; Zatloukalova, Martina; Dvorakova, Petra; Coufalova, Dominika; Novak, David; Hernychova, Lenka; Vacek, Jan (Free radical biology & medicine, 2017)
Proteins are subject to oxidative modification and the formation of adducts with a broad spectrum of reactive species via enzymatic and non-enzymatic mechanisms. Here we report that in vitro non-enzymatic methylglyoxal (MGO) binding causes the inhibition and formation of MGO advanced glycation end-products (MAGEs) in Na+/K+-ATPase (NKA). Concretely, MGO adducts with NKA amino acid residues (mainly Arg) and Nε-(carboxymethyl)lysine (CML) formation were found. MGO is not only an inhibitor for solubilized NKA (IC50=91±16μM), but also for reconstituted NKA in the lipid bilayer environment, which was clearly demonstrated using a DPPC/DPPE liposome model in the presence or absence of the NKA-selective inhibitor ouabain. High-resolution mass spectrometric analysis of a tryptic digest of NKA isolated from pig (Sus scrofa) kidney indicates that the intracellular α-subunit is naturally (post-translationally) modified by MGO in vivo. In contrast to this, the β-subunit could only be modified by MGO artificially, and the transmembrane part of the protein did not undergo MGO binding under the experimental setup used. As with bovine serum albumin, serving as the water-soluble model, we also demonstrated a high binding capacity of MGO to water-poorly soluble NKA using a multi-spectral methodology based on electroanalytical, immunochemical and fluorimetric tools. In addition, a partial suppression of the MGO-mediated inhibitory effect could be observed in the presence of aminoguanidine (pimagedine), a glycation suppressor and MGO-scavenger. All the results here were obtained with the X-ray structure of NKA in the E1 conformation (3WGV) and could be used in the further interpretation of the functionality of this key enzyme in the presence of highly-reactive metabolic side-products, glycation agents and generally under oxidative stress conditions.
Keywords: Cattle; Animals; Kidney; skot; Sodium-Potassium-Exchanging ATPase; oxidační stres; Reactivity; Sus scrofa; vazba proteinů; Oxidative Stress; sérový albumin hovězí; Mass spectrometry; Glycation End Products, Advanced; Serum Albumin, Bovine; Oxidative post-translational modification; Aminoguanidine; pyruvaldehyd; krystalografie rentgenová; hmotnostní spektrometrie; Ouabain; ouabain; Protein Conformation; guanidiny; Enzyme inhibition; produkty pokročilé glykace; Mass Spectrometry; konformace proteinů; Sodium pump; Pyruvaldehyde; zvířata; Crystallography, X-Ray; ledviny; Protein Binding; sodíko-draslíková ATPasa; Guanidines; Methylglyoxal